Postcolonial sociology - Go, Julian 1970- (Emerald, 2013)
Postcolonial theory has enjoyed wide influence in the humanities but for social science, and in particular sociology, its implications remain elusive. This special volume brings together leading sociologists to explore the concept of "postcolonial sociology," with brand new postcolonial readings of canonical thinkers like Karl Marx, Max Weber, Emile Durkheim and Robert Park. Chapters consider whether or not postcolonial theory is compatible with sociology; explore the relationship between knowledge and colonial power; and offer critical perspectives on the sociology of race and the implications of postcolonial theory for global sociology. They also unravel the complex entanglements of sociology, area studies, and postcolonial studies; give creative deployments of postcolonial concepts such as hybridity; and critical excavations of sociological thought in India and Mexico. In sodoing this volume is among the first to craft newsociologiesinformed by postcolonial criticism.